SOFC Cathode Degradation Due to Salt Contamination. (30th May 2017) - Thambiraj, Nelson; Suciu, Crina; Waernhus, Ivar; Vik, Arild; Hoffmann, Alex C.
Abstract : In the course of a larger project aimed at determining the robustness of off-shore solid oxide fuel cell (SOFC) installations and the nature and underlying causes for any cell degradation in a marine environment, short-term and long-term cell testing were carried out to ascertain the effect of salt (NaCl) contamination in the feed to the SOFC cathode on the cell performance, and, in the event of degradation due to the presence of the salt, determine the underlying cause of degradation of the performance. Both the short-term and long-term performance were shown by the I-V curves to be degrading due to the presence of salt in the cathode feed. SEM/XRD analyses made it possible to identify NaCl taken up in the cathode microstructure after the short-term testing but the cell structure was seen to remain intact. The long-term degradation was found to be much more severe and the SEM images showed clear indications of delamination at the cathode/electrolyte interface with salt present in the feed to the cathode, something that was not seen after long-term testing without salt presence.